Proposed Social Media Marketing Strategy to Increase Brand Awareness And Purchase Intention For Indonesia Muslim Brand (Case of Local Brand Irna La Perle) - Tasya, Ratu Tifa Prima; Astuti, Novika Candra (PT. EQUATOR SINAR AKADEMIA, 2025)
This study addressed the challenge faced by Irna La Perle, a prominent Indonesian Muslim fashion brand, which suffered from limited digital presence and low engagement rates despite a substantial follower base. This situation hampered the brand’s ability to enhance brand awareness and purchase intention, particularly among younger, tech-savvy Muslim consumers. Intense competition from more digitally agile local brands further exacerbated this issue, underscoring the urgent need for Irna La Perle to implement a targeted and interactive social media marketing strategy tailored to evolving consumer behaviors within Indonesia’s Muslim fashion market. Employing a mixed-methods approach, combining quantitative and qualitative analyses, the study integrated internal and external assessments alongside strategic business solutions using the RACE Framework and TOWS Matrix. Findings revealed that social media marketing influenced Irna La Perle’s brand awareness and purchase intention but was underutilized, especially for its daily wear segment. Despite a strong Instagram following, actual brand recognition among Gen Z and Millennials remained low, largely due to promotional focus on premium bridal collections rather than accessible daily wear. Purchase intention showed similar limitations, with most consumers expressing only moderate willingness to buy after engaging with the brand’s content. This gap stemmed from weak storytelling, limited product differentiation, and a mismatch with younger consumers’ preferences.